UJI KUALITATIF ZAT PEWARNA SINTETIS PADA JAJANAN MAKANAN DAERAH KETAPANG KOTA BANDA ACEH - Subhan; Arfi, Febrina; Ummah, Aminul (Department of Chemistry, Faculty of Science and Technology, UIN Ar-Raniry, 2019)
The synthetic dyes Rhodamin B and Methanyl Yellow are still often added to snacks to make the colors of snacks more obvious and people are interested in consuming them. Its use in long-term food products can cause cancer. The purpose of this study was to analyze synthetic dyes in chips, red macaroni, steamed cakes, yellow macaroni, bread jam and guava juice around the Ketapang area of ​​Banda Aceh City. The research method used is the Spot Test Analysis conducted qualitatively at the LPPOM MPU Laboratory in Banda Aceh City. The test results on the three samples namely chips, red macaroni, and steamed cake did not produce a color change reaction that showed Rhodamine B. The test results on yellow macaroni, bread jam and guava juice showed that the three samples tested did not produce a color change reaction indicating the presence of Methanyl Yellow. The conclusion from this test is that snacks have not been identified as Rhodamin B and Methanyl yellow or are free from the contents of the two synthetic dyes.